Desenvolvimento de um aparelho auditivo de tecnologiaaberta por dois grupos de pesquisa de universidades: um caso de fonte aberta - Joao Gabriel Alves Ribeiro Rosa (2018)
This work aims to present the development of a product (a hearing aid) by university laboratories, in order to stimulate the social innovation, assimilating the role of open innovation practices in this kind of project and also analysing the university's role in the promotion and creation of this profile of initiatives. This is based on the participatory research methodology resulting in the understanding of how technology development is conducted in social innovation projects. It introduces the context of how the network cooperation is formed, discusses about various factors that influence in the development of the project and analyses the ideological and structural context